Peran Penggunaan Teknologi Digital Terhadap Kesuksesan dan Kegagalan E-bisnis di Era Digital - Muhammad Deary; Gilang Dwi Prasetyo; Rohid Akbar; M Yuda Al- Faruq; Nurbaiti Nurbaiti (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2025)
In current technological advances, digital technology has developed rapidly in assisting human activities, for example in the business sector. In today's digital era, technology plays an important role in the changes that occur in business activities, which previously could only be done face to face between the seller and the buyer, now with only e-commerce technology, buyers do not have to meet the seller to buy the product or service they need. . However, when using e-commerce technology, you must pay attention to what is needed between buyers who want to look for the goods or services they need and sellers who sell their goods or services so that when the business process occurs there will be no failure later.